2019
DOI: 10.32607/20758251-2019-11-1-48-57
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dipeptide NGF Mimetic GK-2 Selectively Activating the PI3K/AKT Signaling Pathway Promotes the Survival of Pancreatic β-Cells in a Rat Model of Diabetes

Abstract: We investigated the cytoprotective effect of a novel low-molecular-weight NGF mimetic, GK-2 (hexamethylenediamide bis-N-monosuccinyl-L-glutamyl-L-lysine), on pancreatic -cells. The neuroprotective effect of GK-2 had been previously shown to be associated with selective activation of the PI3K/Akt signaling pathway. In this study, rats with streptozotocin (STZ)-induced type 2 diabetes mellitus were used. Metformin was used as a reference drug. STZ was immunohistochemically demonstrated to reduce the number of -c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…72,73 In hypoxic conditions, it can reduce damage to the body by regulating the expression of target genes coding for downstream factors related with the hypoxic response, and by modulating cell energy metabolism, glucose metabolism and apoptosis. 74 Studies have shown that oxidative stress and 75 Antioxidant therapy can increase the expression of medullary HIF in diabetic kidneys and improve renal oxidative damage. 76 HIF activation can attenuate changes in renal oxygen metabolism and mitochondrial function caused by diabetes, thereby reducing proteinuria and improving renal tubular interstitial damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…72,73 In hypoxic conditions, it can reduce damage to the body by regulating the expression of target genes coding for downstream factors related with the hypoxic response, and by modulating cell energy metabolism, glucose metabolism and apoptosis. 74 Studies have shown that oxidative stress and 75 Antioxidant therapy can increase the expression of medullary HIF in diabetic kidneys and improve renal oxidative damage. 76 HIF activation can attenuate changes in renal oxygen metabolism and mitochondrial function caused by diabetes, thereby reducing proteinuria and improving renal tubular interstitial damage.…”
Section: Discussionmentioning
confidence: 99%
“…77 The PI3K-Akt signaling pathway plays an important role maintaining insulin stability. 75 This signaling pathway is activated by many types of cellular stimuli or toxic insults and regulates fundamental cellular functions, such as transcription, translation, proliferation, growth, and survival. 76 At present, there are studies showing that selective activation of the PI3K/AKT signaling pathway can modulate neuroprotection, angiogenesis, and islet b cell survival in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Под действием высоких доз СТЗ (50-70 мг/кг) у крыс наблюдается до 90 % деструкции панкреатических β-клеток, что соответствует экспериментальной модели СД 1 типа [2], в то время как инъекции более низких доз СТЗ (40-45 мг/кг), дробное многократное введение малых доз [3] или предшествующая защита поджелудочной железы никотинамидом вызывают умеренную гипергликемию при потере 40-50 % активных β-клеток, что может свидетельствовать о моделировании СД 2 типа [4]. Ранее нами отмечалось сохранение 48 % жизнеспособных β-клеток в экспериментах на крысах при введении СТЗ в дозе 45 мг/кг, вызывающей выраженную гипергликемию до 28,5 ммоль/л [5].…”
Section: введение / Introductionunclassified
“…Since GK‐2 has not been studied in a model of prediabetes, the purpose of this work is to assess it effects in condition of prediabetes induced by obesity. Previously, we have proven the GK‐2 cytoprotective effect toward pancreatic β‐cells 29 . Тaking into account the role of liver as the other target organ for prediabetes and T2DM it seemed appropriate along with the standard functional prediabetes signs (fasting and postprandial glycaemia levels, morphometric parameters of obesity, lipid metabolism indicators) to study the effect of GK‐2 on the histological structure of the liver.…”
Section: Introductionmentioning
confidence: 99%